Kemampuan Pemecahan Masalah Matematis melalui Pembelajaran Berbasis Masalah dengan Scaffolding - Mohamad Gilar Jatisunda; Dede Salim Nahdi (Universitas Hamzanwadi, 2020)
One of the main goals of school mathematics is the achievement of mathematical problem-solving abilities through problem-based learning. It is expected that these abilities can be achieved well by students. However, the complexity of the problem and minimum confidence become a problem when students experience complex situations created in the problem-based learning process. Scaffolding becomes essential because of the differences in each student's knowledge stored in long term memory. The purpose of the study was to analyze differences in mathematical problem-solving abilities with two different learning and based on initial mathematical abilities. Learning in the experimental class is problem-based learning with scaffolding, and then control class learning is problem-based without scaffolding. The research method used was a quasi-experimental design with a matching-only pretest-posttest control group design. Sample selection using purposive sampling to get samples with the same characteristics, the total number of samples is 60 students with each division 30. The initial mathematics ability has the same role in the mathematical problem-solving ability in the experimental and control classes. That is when students are in the high category then the ability of severe mathematical problem-solving. However, when the two classes are compared, the results are significantly different. Scaffolding becomes a factor that distinguishes the ability to solve mathematical problems.